2008
DOI: 10.1177/0032885508322453
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Factors Contributing to Institutional Misconduct

Abstract: Importation and deprivation theories are typically offered to explain the process by which inmates adjust to prison environments. Nearly all prior empirical tests of these theories have exclusively relied on samples of male inmates. Using self-report and official data from 247 male and female inmates confined to correctional institutions in a southeastern state, this study makes an important contribution to the correctional literature by examining whether theoretical predictors of infraction behavior are simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 54 publications
12
134
2
Order By: Relevance
“…Some studies found African-Americans to be disproportionately involved in prison misconduct (Fernandez & Neiman, 1998;Goetting & Howsen, 1983, 1986Toch et al, 1989). Gover, Perez, and Jennings (2008) suggested that the effect may be gender specific: nonwhite females, on average, had a higher number of infractions than white females, but the effect of race was nonsignificant among male inmates. The race/ethnicity effect may also be contingent upon the type of misconduct.…”
Section: Factors Associated With Prison Misconductmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found African-Americans to be disproportionately involved in prison misconduct (Fernandez & Neiman, 1998;Goetting & Howsen, 1983, 1986Toch et al, 1989). Gover, Perez, and Jennings (2008) suggested that the effect may be gender specific: nonwhite females, on average, had a higher number of infractions than white females, but the effect of race was nonsignificant among male inmates. The race/ethnicity effect may also be contingent upon the type of misconduct.…”
Section: Factors Associated With Prison Misconductmentioning
confidence: 99%
“…In addition, individuals with higher educational attainment should be better able to think critically, which would make them more inclined to fully assess and appreciate the consequences of their actions (Harer & Langen, 2001). Indeed, several researchers have found that inmates with higher levels of education are less likely to engage in misconduct (Adams, 1977;Fernandez & Neiman, 1998;Gover et al, 2008;Toch et al, 1989). The effect of educational attainment, however, may depend on the measure of misconduct.…”
Section: Factors Associated With Prison Misconductmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Steiner and Woolredge (2008) reported that participation in drug treatment, education, and vocational programming actually increased misconduct in their study, other research has reached a different conclusion. For example, Gover, Perez, and Jennings (2008) found that employment in prison reduced disciplinary infractions. Similarly, in a more recent study by Steiner and Woolredge (2014), they found that the number of hours spent per week in a work assignment was negatively associated with both violent and nonviolent misconduct.…”
Section: Prior Research On Prison Misconductmentioning
confidence: 99%
“…Prisons risk classification schemes consistently reference prior offending and past violence as part of their security and placement assessment of individuals both while they are incarcerated and during placement in the community (Gaes et al, 2002;Gendreau, Goggin & Law, 1997;Gover, Perez & Jennings, 2008;Harer & Langan, 2001;Harer & Steffensmeier, 1996;Greenfeld & Snell, 1999;Kury & Smartt, 2002;Skeem & Louden, 2006). In the context of these assessments, some research indicates that these contributory factors to prison violence are the same for males and females (albeit at different levels) (Harer & Langan, 2001) while other research suggests that the predictive factors are significantly and in some instances inversely predictive of different kinds of institutional behavior across genders Gover et al, 2008). These inquiries have often emerged as elements of the scientific debate over importation theory and deprivation theory and the relative significance of pre-existent as contrasted to situational factors in predicting various aspects of prison adjustment (Faily & Roundtree, 1979;Craddock, 1996;Thompson & Loper, 2005 Study Analyses.…”
Section: Outcomes Associated With Instant Offense and Prison Sentencementioning
confidence: 99%